The External Obturator Footprint Is a Usable, Accurate, and Reliable Landmark for Stem Depth in Direct Anterior THA. Issue 8 (August 2021) - Vles, Georges; Meynen, Alexander; De Mulder, Jef; Ghijselings, Stijn
Abstract: Background: Previous CT and cadaver studies have suggested that the external obturator footprint might be used as a landmark for stem depth in direct anterior THA. Instructions on where to template this structure with small variability in height have been developed but have not been tested in daily clinical practice. Questions/purposes: In this study we sought to investigate the (1) usability, (2) accuracy, and (3) reliability of the external obturator footprint as a landmark for stem depth in direct anterior THA. Methods: The distance between the superior border of the external obturator tendon and the shoulder of the stem was measured intraoperatively in all patients (n = 135) who underwent primary THA via a direct anterior approach performed by the senior author between November 2019 and October 2020. The landmark was considered useful when two of thre`e evaluators agreed that the intersection of the vertical line comprised of the lateral wall of the trochanteric fossa and the oblique line formed by the intertrochanteric crest was clearly visible on the preoperative planning radiograph, and when the landmark was furthermore identified with certainty during surgery. Accuracy was defined as the degree of agreement (categorical for thresholds of 2 and 5 mm, the latter representing the threshold for developing unphysiological gait parameters) between the intraoperative distance and radiographic distance as measured on intraoperative fluoroscopy images or postoperative radiographs, which were calibrated based on femoral head sizes in a software program commonly used for templating. Intrarater reliability was defined as the degree of agreement (categorical for thresholds of 1 mm, which we considered an acceptable measurement error) between the ratings of one observer, who measured the radiographic distance on two different occasions separated by a washout period of at least 2 weeks. Interrater reliability was defined as the degree of agreement (categorical for thresholds of 1 mm, which we considered an acceptable measurement error) between the ratings of three observers with varying levels of experience (a fellowship-trained hip surgeon, a hip surgery fellow, and a medical student). Results: The landmark was considered useful in 77% (104 of 135) of patients who underwent direct anterior THA based on the observations that the trochanteric fossa was clearly visible on the planning radiograph in 117 patients and that the tendon was identified with certainty during surgery in 118 patients. There was good-to-excellent accuracy (intraclass correlation coefficient 0.75-087), and intrarater reliability (ICC 0.99) and interrater reliability (ICC 0.99) were both excellent. Conclusion: This clinical study showed that the external obturator footprint is a useful, accurate, and reliable landmark for stem depth in direct anterior THA. Clinical Relevance: The external obturator landmark allows the surgeon to position the stem within a range of the templated depth that is beneath the threshold for the development of unphysiological gait parameters. Although strictly speaking it was found useful in 77% of patients in this study, we found that this percentage of usability can easily be improved to around 90% by providing the radiology lab technician with instructions to correct external rotation of the foot during the taking of the planning radiograph. Future studies could compare the established (in)equality in leg length in patients using the external obturator landmark with computer-assisted surgery.